Quantifying nitrate pollution sources of shallow groundwater and related health risks based on deterministic and Monte Carlo models: A study in Huaibei mining area, Huaibei coalfield, China - Huili Qiu; Herong Gui; Haifeng Xu; Lin Cui; Zhichun Li; Hao Yu (Ecotoxicology and Environmental Safety, 2023)
Nitrate pollution in groundwater is a global environmental concern. As a result, accurate identification of potential sources for such pollution is of critical significance to the effective control of groundwater quality. In this study, forty-nine shallow groundwater samples were collected from the Huaibei mining area. Hydro-chemical characterization, geospatial analysis technique, dual nitrate isotopes (δ15N-NO3- and δ18O-NO3-), Bayesian model and health risk assessment model were adopted for exploring the conditions, sources, proportion, and potential health risks of nitrate pollution for the first time in the study area. The results showed that the nitrate concentration ranged from 0.00 to 293.21 mg/L, and that 18.37% groundwater samples exceeded the standard of drinking water in China (GB 5749–2006). Based on the dual isotopic values of nitrate, it could be concluded that nitrification was dominated migration and transformation process of nitrogen. The results of Bayesian model showed that the proportional contributions of the potential nitrate pollution sources in shallow groundwater were manure and sewage (M&S) (39.54 %), NH4+ in fertilizer and precipitation (NHF&P) (34.93 %), soil nitrogen (SN) (14.89 %), and NO3- in atmospheric deposition (NAD) (10.64 %). The health risk assessment indicated that non-carcinogenic risks posed by NO3--N was higher for children than adults. The primary exposure pathway was oral ingestion. Monte Carlo simulation were applied to evaluate model uncertainty. The probabilities of non-carcinogenic risks were up to 12.54 % for children and 5.22 % for adults. In order to protect water quality and drinking water safety, it was suggested that effective nitrate reduction strategies and better management practices can be implemented.